Assessment of the activities physiological cost of the defense forces officers in Ukraine using miniature ECG device - Bocharov, Mykhailo; Stasiuk, Vasyl; Osyodlo, Vasyl; Ryzhenko, Tetyana; Malanin, Vlad; Chumachenko, Dmytro; Chaikovsky, Illya (Frontiers in Cardiovascular Medicine, 2023)
In the principles of the organization of armed struggle of the defense forces of most developed countries of the world, considerable attention is paid to the evaluation of combat readiness of the military personnel. This procedure is conditioned by such interconnected goals of the armed struggle as the maximum realization of the combat potential and the minimization of personnel losses. The purpose of the work is to determine the physiological cost of the activities of the soldiers of the Defense Forces of Ukraine with the help of miniature electrocardiographic hardware and software complexes. In the research, ultra-miniature ECG devices worn on the body for a long time, so-called wearable "on-body" ECG patch devices, were used in various combat conditions. When analyzing the data, the principle of multi-faceted ECG analysis was implemented, which allows you to obtain complete and physiologically based information, which includes 4 blocks: heart rate variability (HRV), amplitude-time indicators of the ECG, heart rhythm disorders, and psycho-emotional state. In this study, a complex index of the functional state formed based on estimates of generally accepted and original indicators of heart rhythm variability, the shape of the teeth and complexes of the electrocardiogram, as well as an index of the psycho-emotional state formed according to the same principles based on the analysis of heart rhythm variability according to the modified McCraty algorithm (USA) was evaluated. Examination with the help of the complex is carried out in a state of rest, sitting or lying down. The sensitivity of the developed monitoring system is good enough to detect the changes in the functional state both in the case of short-term (for hours) intense physical or psycho-emotional stress and more chronic (for days and weeks) stress depending on the nature of the task being done. The proposed methods and means can be considered an important tool to support the commander's decision-making regarding the ability of personnel from the point of view of their functional state to perform combat tasks.